A Study on Properties of Concrete as a Potential Innovative of Coarse Aggregate with Coconut Shell - Azahar, Anis Faezah; A. Rahman, Noor Khazanah (Progress in Engineering Application and Technology, 2021)
The excessive exploitation of natural aggregate in producing concrete seems like a significant problem that increases the chance of depleting natural resources. This paper presents coconut shell potential as a replacement for coarse aggregate and the strength of coconut shell concrete compared to conventional concrete in gradation replacement of 4%, 8%, and 12%. A total of 24 cubes of 100mm x 100mm x 100mm were cast and tested to determine the concrete’s density, water absorption, and compressive strength. The coarse aggregate was replaced with a coconut shell size 10-14mm for concrete grade M20. The test results showed the conventional concrete increase’s compressive strength while the concrete coconut shell shows vice versa. However, the concrete coconut shell resulted in high density where it suitable for lightweight concrete. The result indicated that the concrete with 12% replacement of coconut shell is suitable for producing lightweight concrete.